(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
هدفت الدراسة إلى إجراء التقييم المالي لصالة زراعة محمية مزروعة بالبندورة المسمدة عضوياً مساحتها 800 م2 من خلال حساب التكاليف والإيرادات، وباستخدام بعض المؤشرات الاقتصادية بالاستناد إلى بيانات ومعطيات أولية تم جمعها من موقعي البحث (رأس العين، الخراب)، وبالاعتماد على المنهج الوصفي التحليلي، حيث أظهرت النتائج أن الربح السنوي الصافي 149980.4 ل.س وزمن استعادة رأس المال المستثمر 1.3 سنة، معدل العائد البسيط 1.72 ل.س/ وحدة إنفاق، معدل العائد المحاسبي172 %. إذاً، أظهرت الدراسة أن الزراعة العضوية تحقق أرباحاً مضمونة، وخلال فترة زمنية قصيرة، إذا ما توفرت مستلزمات الإنتاج الأساسية بأسعار مناسبة، وخاصة الأسمدة العضوية والبذور، مع تأمين تسويق المنتج بأسعار مناسبة من خلال الشهادات العضوية. The Purpose of this research is Financial evaluation for green house organic tomato hall in Syria its survey 800m2, taking in account the costs and returns, by using some of economic criteria, according to the information presented from the location of study (Ras-Alaen, Alkhrab) and depending on analysis description approach, the results revealed: Net Annual Returns 149980.4 Syrian pounds, Recovery Time of Costs Invests 1.3 year, Simple Rate of Return 1.72 Syrian pounds. So, the organic agriculture achieves absolute returns within a short period of time if we have a main production requirements with suitable prices specially organic fertilizers and seeds, and if the organic product is marketed with appropriate prices by organic certification.